The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0891241620914961
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Five Cents: Mismatched Meaning Making at a Bottle and Can Redemption Center

Abstract: Drawing on a year-long ethnography at a non-profit bottle and can redemption center, this study examines the mismatched meanings ascribed by recyclers (or “canners”) and redemption center management to recycling work. Canners primarily make sense of the work for the money it puts in their pocket and for its autonomous work conditions. By contrast, management imbues canning with moral meaning, linking recycling to social, environmental, and spiritual good. I argue that disputes over organizational policies can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…We propose that the foundations of this disagreement may be partly due to a mismatch between the frames of employees and managers. Iverson (2020) found that mismatched meanings of work created tension between workers and managers in a single work site. More generally, theory and research in organizational behavior on person–organization fit (Kristof‐Brown, Zimmerman, and Johnson 2005) and competing values (Cameron and Quinn 2011) has established the importance of employee perceptions that their values are compatible with those of the organization.…”
Section: Employees’ Frames and Sensemakingmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that the foundations of this disagreement may be partly due to a mismatch between the frames of employees and managers. Iverson (2020) found that mismatched meanings of work created tension between workers and managers in a single work site. More generally, theory and research in organizational behavior on person–organization fit (Kristof‐Brown, Zimmerman, and Johnson 2005) and competing values (Cameron and Quinn 2011) has established the importance of employee perceptions that their values are compatible with those of the organization.…”
Section: Employees’ Frames and Sensemakingmentioning
confidence: 99%
“…Liao et al (2009) found that managers and employees within the same organization had significantly different perspectives on the nature of that organization's HR system. In an ethnographic study,Iverson (2020) identified mismatched meanings of work as a source of friction between managers and employees.4 Compared with the four-part framework we use,Heery (2016) focuses on three frames by combining the neoliberal-egoist and unitarist frames, which disguises important differences in these two frames that have unique predictions for HR practices Godard's (2017). intent is to develop perspectives on macro-level governance of the employment relationship, which leads to distinct pluralist and liberal reformist perspectives, but this distinction is unnecessary for our application because the withinorganization implications are very similar.…”
mentioning
confidence: 99%
“…Second, small incentives may not be sufficiently motivating for people to engage in the behavior. For example, some recycling policies provide $0.05 or $0.10 for each bottle returned (Iverson, 2020), which follows the continuous reinforcement schedule but the amount may be too small for most people. A potentially more effective intervention is to change this policy to a variable ratio schedule that provides a larger financial reward after a variable number of bottles returned (e.g., instead of receiving $0.10 per bottle, there is a 1% chance of getting $10 per bottle).…”
Section: Waste Behaviorsmentioning
confidence: 99%
“…Beyond cost concerns, cognitive biases (e.g., status quo bias, present bias) can prevent people from taking climate action . Finally, tangible rewards for climate action, such as rebates for purchasing EVs, and receiving $0.10 for every recycled bottle, are often rare, too infrequent, or too small to meaningfully change behavior (Helveston et al, 2015;Iverson, 2020).…”
Section: Introductionmentioning
confidence: 99%